Using of Folk Art to Enhance Learning at English Lessons in Primary School - Tetyana Blyznyuk; Karolina Nafalska (Vasyl Stefanyk Precarpathian National University, 2017)
In today's multicultural space we can feel reassessment of existing paradigms of education in view of globalization changes, interstate cooperation in cultural and educational spheres. The article highlights the problem of human adaptation to foreign cultural environment, the contents of ethnographic knowledge, the needs of modern European and global integration. So the paper analyzes and interprets the urgent the idea of using ethnographic materials, including folk art, in teaching humanities and arts subjects in primary school, particularly in native and foreign languages, reading, science, music, manual work, etc.